Analisis Earning Per Share (EPS) Dan Net Propit Margin (NPM) Terhadap Harga Saham - Dedi Karmana; Ryan Noer Sofia (LPPM POLITEKNIK LP3I BANDUNG, 2019)
The purpose of this research is to know : 1) the influence Earning Per Share (EPS), the stock price at PT. Unilever Indonesia Tbk. 2012-2018 period. 2) the influence Net Profit Margin (NPM), the stock price at PT. Unilever Indonesia Tbk. 2012-2018 period. 3)Influence Earning Per Share (EPS) and Net Profit Margin (NPM) simultaneously to the stock price on PT. Unilever Indonesia Tbk. 2012-2018 period. The method used is a quantitative method with a type of decision study approach and literature study and documentation approach. Data yang digunakan adalah data sekunder dari laporan keuangan dan/atau annual report dengan mengakses www.idx.xo.id Adapun alat analisis yang digunakan adalah analisis regresi linear berganda dengan menggunakan uji asumsi klasik dan uji hipotesis dan di analisis menggunakan aplikasi SPSS versi 25. The results showed: 1) Earning Per Share (EPS) has a significant effect on stock prices. 2) Net Profit Margin (NPM) has no significant effect on stock prices. Earning Per Share (EPS) and Net Profit Margin (NPM) have a simultaneous effect on stock prices.